Addictionology a medical specialty and sub-specialty of psychiatry: La adiccionología una especialidad médica y subespecialidad de la psiquiatría - Nizama Valladolid, Martín (2019)
Addictionology as a component of the health sciences is rapidly becoming recognized as a medical discipline, specifically as a subspecialty of psychiatry. The problem of addictions is a subject that extends and worsens in postmodern society, due to its multidimensionality and multifactoriality. The health conditions of the countries have improved in terms of reducing mortality and the incidence of some communicable diseases. However, there is a greater incidence of chronic noncommunicable diseases related to lifestyles, as well as the emergence of health problems derived from violence, drug consumption, social, recreational addictions and digital addiction (connectivity). Family factors, including rejection by parents and family conflicts, due to substance abuse and mental health problems, are among the strongest and most consistent predictors of adolescent behavior problems. Therefore, in the Holistic Family Centered Model, Nizama proposes integral human development through multidimensional organization as an axis of life that comprises eleven dimensions of human life: body, genetic potential, personality, human essence, cognition, imagination, lifestyles, assets, image, futurity and posterity. In conclusion, addictionology is the medical specialty indicated for the successful and hopeful management of this volitional disease in all age groups, with committed and sustainable family adherence. DOI:10.25176/RFMH.v19.n2.2078